Business Law Construction on ESG Practices in the Electric Vehicle Industry: Measuring Economic Growth and Ecological Impacts - habibi habibi; Febrian Chandra; Rizki Apriadi Bahri; Rifki Purwadi; Usman Usman (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2026)
The rapid expansion of the electric vehicle (EV) industry in Indonesia promises significant economic growth through nickel downstreaming but simultaneously poses massive ecological threats. This paper aims to analyze the juridical construction of Environmental, Social, and Governance (ESG) practices within Indonesian business law to balance economic investments with sustainable ecological protection. Employing a normative-juridical method through statutory and conceptual approaches, this study strictly examines corporate and environmental legal frameworks without sociological elements. The findings reveal a regulatory vacuum where ESG compliance remains a voluntary soft law rather than an imperative hard law for closed corporations in the EV supply chain. Existing regulations lack the integration of ecological compliance into the absolute obligations of corporate governance. Consequently, business law must be reconstructed to enforce supply chain liability, mandatory green accounting, and Extended Producer Responsibility (EPR). The conclusion emphasizes that integrating ESG as a doctrinal pillar in commercial and corporate law is a conditio sine qua non to ensure that the EV industry's macroeconomic growth does not compromise the environmental carrying capacity and the fundamental rights of future generations.